Analisis Program Badan Layanan Umum Daerah (BLUD) Sekolah Menegah Kejuruan (SMK) Dalam Mewujudkan Layanan Pemerintah Daerah Yang Good Corporate Governance (GCG): Studi Pada SMK Negeri 5 Surabaya - Ardatila Puspita (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The Regional Government, in supporting education reform for better quality and optimality within its units of authority, established the Regional Public Service Agency Program (BLUD) which can be understood as a system implemented by a technical implementation unit of regional agencies/agencies in providing services to the community, and has flexibility in financial management as an exception to regional financial management provisions in general. In line with the Directorate of Vocational High School Development (SMK) in seeking SMK as a school with BLUD status, this can support the management of goods and services whose superior products can manage the production process in the Teaching Factory Program (TEFA) more flexibly without violating regulations (Fazli, 2022). Implementing the Teaching Factory (TEFA) in the form of goods and services for vocational school students is expected to align with the objectives of Good Corporate Governance (GCG) Regional Government Services, namely good management to support the BLUD Vocational School Program in schools. In conducting this research the author used a descriptive qualitative research method approach.